272 Fluctuation, invisibility, fatigue the barriers to maintaining employment in SLE: results of an on-line survey. (April 2019) - Booth, Sara; Walker, Elizabeth; Price, Elizabeth
Abstract : Background: It is well-documented that systemic lupus erythematosus (SLE) is associated with high levels of workplace disability and unemployment. The objective of this study was to understand reasons for this and to describe the barriers and facilitators to employment identified by people with SLE to develop appropriate solutions. Unemployment, as well as unsuitable work, has adverse health outcomes. Methods: Adults with SLE completed a UK-specific online survey, through the LUPUS UK website, designed to find out more about the difficulties and successes that people with SLE have in maintaining employment. The survey was predominantly qualitative, to understand participants employment experiences to generate possible solutions. Results: 393 people gave detailed responses to the survey within eight weeks. Every respondent reported a detrimental effect of SLE on their ability to work. 40.45% had left employment because of it. The themes of concern to respondents were unambiguous (i) the difficulties of working (and career damage) with SLE (ii) long-term fear and anxiety overshadowing work/family life (iii) the greater potential to remain in some/employment when modifications of work pattern and support from management and colleagues were available. Anti-disability discrimination was reported as partially helpful but incomplete, omitting many features of lupus disability. SLE-related fatigue, its invisibility and fluctuating nature were felt to be the main barriers to maintaining employment. Many respondents could work only part time, anxiety was high regarding future ability to continue working and financial strains. Many had taken substantial pay reductions and refused offered promotions to preserve their health. Distress due to loss of work and the benefits it brings were reported by every respondent who had left work. Loss of work and the demeaning impact of a widespread lack of understanding of the reasons for workplace disability had a detrimental effect on individuals mental health. Conclusions: SLE presents specific difficulties for maintaining employment fatigue, fluctuation and invisibility not addressed by current anti-discrimination legislation or currently-available reasonable adjustments. This study demonstrates that (i) employment is an important area of concern for people with SLE (ii) SLE has significant detrimental effects on individuals' ability to participate and progress in employment (iii) legislators and employers need information about SLE as invisibility and fluctuation cause hidden problems (ii) more data is needed to inform workplace adjustments if individual distress and societal loss of skills are to be addressed. Funding Source(s): No external funding required